2019
DOI: 10.1021/acsmedchemlett.9b00218
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Potent N-Ethylurea Pyrazole Derivatives as Dual Inhibitors of Trypanosoma brucei and Trypanosoma cruzi

Abstract: Trypanosoma brucei (T. brucei) and Trypanosoma cruzi (T. cruzi) are causative agents of parasitic diseases known as human African trypanosomiasis and Chagas disease, respectively. Together, these diseases affect 68 million people around the world. Current treatments are unsatisfactory, frequently associated with intolerable side-effects, and generally inadequate in treating all stages of disease. In this paper, we report the discovery of N-ethylurea pyrazoles that potently and selectively inhibit the viability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Treatment options for Chagas disease remain limited. Efforts to expand the scope of chemical scaffolds for drug discovery programs against T. cruzi using natural product, de novo design, and drug repositioning approaches have yielded promising new leads in recent years 9,16,[22][23][24][25] . Here, we used a high-throughput screening and bioactivity-guided fractionation pipeline to identify five potent leucinostatins from an Ophiocordyceps sp.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment options for Chagas disease remain limited. Efforts to expand the scope of chemical scaffolds for drug discovery programs against T. cruzi using natural product, de novo design, and drug repositioning approaches have yielded promising new leads in recent years 9,16,[22][23][24][25] . Here, we used a high-throughput screening and bioactivity-guided fractionation pipeline to identify five potent leucinostatins from an Ophiocordyceps sp.…”
Section: Discussionmentioning
confidence: 99%
“…brucei or T . cruzi+/- fibroblasts from in-vitro cultures as described previously [ 20 ]) were added at a concentration of 1:10 (B-cell: infected cell), as measured before lysis. Parasite and cell lysates were prepared in B-cell medium by 10 freeze/thaw cycles.…”
Section: Methodsmentioning
confidence: 99%
“…TLR7 agonist R848 (Mabtech) was used at 1 μg/ml; anti-BCR (Fab 0 ) 2 anti-IgM (The Jackson Laboratory) was used at 5 μg/ml, and IFN-γ (Peprotech) at 100 U/ml. Uninfected (3T3 mouse fibroblasts) and infected parasite lysates (P. yoelii 17XNL strain from mice-infected blood [12], T. b. brucei or T. cruzi+/-fibroblasts from in-vitro cultures as described previously [20]) were added at a concentration of 1:10 (B-cell: infected cell), as measured before lysis. Parasite and cell lysates were prepared in B-cell medium by 10 freeze/thaw cycles.…”
Section: In Vitro Activation Assaysmentioning
confidence: 99%
“…Pyrazole N-ethylurea derivatives showed potent activity against T. brucei brucei and T. cruzi, with a drastic reduction of parasitemia after 6 days of treatment and efficacy in the murine model of acute T. cruzi infection. The SAR study for N-ethylurea pyrazole derivatives revealed that the meta position in the aromatic ring substantially influences the trypanocidal activity, with the compounds with fluorine and chlorine substituents being the most effective [37].…”
Section: Structure-activity Relationship (Sar) Of Pyrazole Derivativesmentioning
confidence: 99%